Analisis Efektivitas Sistem Pengendalian Internal Melalui Sanksi Adat dalam Upaya Mengatasi Kredit Bermasalah pada Bumdes Merta Nadi di Desa Bayung Cerik - Sopyan pratama Pratama; Nyoman Ayu Wulan Trisna Dewi (Jurnal Akuntansi Profesi, 2021)
This study aims to determine (1) the causes of non-performing loans in BUMDes Merta Nadi in Bayung Cerik Village, (2) strategies and efforts in overcoming non-performing loans at BUMDes Merta Nadi in Bayung Cerik Village, (3) the effectiveness of applying customary sanctions in overcoming the occurrence of non-performing loans on BUMDes Merta Nadi in Bayung Cerik Village. This study uses research methods with a qualitative approach and the type of case study research. Data were collected by means of observation, interviews, and documentation studies. Data analysis techniques in this study include data collection, data reduction, data presentation, conclusions and verification. The results of this study indicate that (1) the causes of non-performing loans in BUMDes Merta Nadi are caused by debtors or external factors, the strategies and efforts made by BUMDes Merta Nadi in overcoming non-performing loans are the strategy of providing credit based on the 5C principle and its efforts by applying customary sanctions as well as administrative sanctions, (3) the application of customary sanctions on BUMDes Merta Nadi is quite effective, because it is able to grow debtor's shame and awareness to pay off arrears, and try to pay off arrears on credit.Keywords: Effectiveness, Internal Control System, Customary Sanctions, Non-performing Loans